Penyuluhan Perilaku Hidup Bersih dan Sehat (PHBS) pada Anak Usia Sekolah Dasar di Desa Buket Medang Ara Kecamatan Langsa Timur - Etika Sari; Intan Bahrina; Yusriati Yusriati (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Elementary school children are an age group that is vulnerable to health problems related to personal and environmental hygiene such as personal hygiene, poor tooth brushing habits and rarely using soap for hand washing. This activity aims to increase knowledge about PHBS and teach children about the procedures for brushing teeth and washing hands properly. The method in this activity is counseling in the form of providing material using visual media as well as direct demonstrations and distribution of leaflets about PHBS to school children so that they can better understand the material that has been given. Participants participated in the socialization activities enthusiastically which resulted in increased understanding of PHBS and how to wash hands and brush teeth properly, so that this can be a good start in improving health rates in elementary school children.